Schooled in murder - Gilbert, Victoria (Gilbert, Victoria. Campus sleuth mystery, 2025)
"Jennifer "Jen" Dalton is an author and educator at Clarion University in Virginia. She loves her job, but some of her petty coworkers look down on her for writing genre fiction. As members of the English department, they wish to encourage students to pursue higher literary aspirations. When a humiliating confrontation between an uppity professor and one of Jen's students, Mia, escalates, no one thinks much of it. Until his dead body is found along with evidence incriminating Mia"--